Causal associations between Helicobacter pylori infection and pregnancy and neonatal outcomes: a two-sample Mendelian randomization study - Huang, Jialyu; Liu, Yuxin; Xu, Dingfei; Chen, Mengyi; Xie, Qiqi; Chen, Jia; Xia, Leizhen; Yu, Lamei; Wu, Qiongfang; Li, Zengming; Wang, Jiawei; Tian, Lifeng (Frontiers in Cellular and Infection Microbiology, 2024)
Background Observational studies have reported that Helicobacter pylori (H. pylori) infection is associated with a series of pregnancy and neonatal outcomes. However, the results have been inconsistent, and the causal effect is unknown. Methods A two-sample Mendelian randomization (MR) study was performed using summary-level statistics for anti-H. pylori IgG levels from the Avon Longitudinal Study of Parents and Children Cohort. Outcome data for pregnancy (miscarriage, preeclampsia-eclampsia, gestational diabetes mellitus, placental abruption, premature rupture of membranes, postpartum hemorrhage) and neonates (birthweight, gestational age, and preterm birth) were sourced from genome-wide association meta-analysis as well as the FinnGen and Early Growth Genetics Consortium. Causal estimates were calculated by five methods including inverse variance weighted (IVW). The heterogeneity of instrumental variables was quantified by Cochran’s Q test, while sensitivity analyses were performed via MR-Egger, MR-PRESSO, and leave-one-out tests. Results IVW estimates suggested that genetically predicted anti-H. pylori IgG levels were significantly associated with increased risks of preeclampsia-eclampsia (odds ratio [OR] = 1.12, 95% confidence interval [CI] 1.01–1.24, P = 0.026) and premature rupture of membranes (OR = 1.17, 95% CI 1.05–1.30, P = 0.004). Similar results were obtained for preeclampsia-eclampsia from the MR-Egger method (OR = 1.32, 95% CI 1.06–1.64, P = 0.027) and for premature rupture of membranes from the weighted median method (OR = 1.22, 95% CI 1.06–1.41, P = 0.006). No significant causal effects were found for other outcomes. There was no obvious heterogeneity and horizontal pleiotropy across the MR analysis. Conclusion Our two-sample MR study demonstrated a causal relationship of H. pylori infection with preeclampsia-eclampsia and premature rupture of membranes. The findings confirm the epidemiological evidence on the adverse impact of H. pylori in pregnancy. Further studies are needed to elucidate the pathophysiological mechanisms and assess the effectiveness of pre-pregnancy screening and preventive eradication.